Canine distemper virus infection among wildlife before and after the epidemic - SUZUKI, Junko; NISHIO, Yohei; KAMEO, Yuki; TERADA, Yutaka; KUWATA, Ryusei; SHIMODA, Hiroshi; SUZUKI, Kazuo; MAEDA, Ken (Journal of Veterinary Medical Science, 2015)
In 2007–2008, a canine distemper virus (CDV) epidemic occurred among wild animals in Wakayama Prefecture, Japan, and many mammals, including the wild boar and deer, were infected. In this study, CDV prevalence among wild animals was surveyed before and after the epidemic. At first, an enzyme-linked immunosorbent assay (ELISA) with horseradish peroxidase-conjugated protein A/G was established to detect CDV antibodies in many mammalian species. This established ELISA was available for testing dogs, raccoons and raccoon dogs as well as virus-neutralization test. Next, a serological survey of wild mammalians was conducted, and it was indicated that many wild mammalians, particularly raccoons, were infected with CDV during the epidemic, but few were infected before and after the epidemic. On the other hand, many raccoon dogs died during the epidemic, but CDV remained prevalent in the remaining population, and a small epidemic occurred in raccoon dogs in 2012–2013. These results indicated that the epidemic of 2007–2008 may have been intensified by transmission to raccoons.